Remarkable influence of alkyl chain lengths on supramolecular hydrogelation of naphthalene diimide-capped dipeptides1. Issue 60 (2nd July 2015) - Zhan, Fu-Kai; Hsu, Shu-Min; Cheng, Hsun; Lin, Hsin-Chieh
<x xml:space="preserve">Abstract</x> The influence of aliphatic chain lengths on supramolecular hydrogelation of naphthalene diimide-capped dipeptides is described.